The power of reinforcement - Flora, Stephen Ray, 1963- (State University of New York Press, 2004)
"According to Stephen Ray Flora, reinforcement is a very powerful tool for improving the human condition despite often being dismissed as regarding people as less than human and as "overly simplistic." This book addresses and defends the use of reinforcement principles against a wide variety of attacks. Countering the myths, criticisms, and misrepresentations of reinforcement, including false claims that reinforcement is "rat psychology," the author shows that building reinforcement theory on basic laboratory research is a strength, not a weakness, and allows unlimited applications to human situations as it promotes well-being and productivity. Also examined are reinforcement contingencies, planned or accidental, as they shape behavioral patterns and repertories in a positive way."--Jacket
Keywords: Reinforcement (Psychology); Reinforcement, Psychology; Renforcement (Psychologie); SELF-HELP -- Motivational & Inspirational.